Konstelasi Calon Tunggal Dalam Pemilihan Umum Kepala Daerah Kaitannya Dengan Konsep Demokrasi (Analisis Terhadap Pemilihan Umum Kepala Daerah Kabupaten Gowa Tahun 2020) - Arfandi Ahmad Permana; Muhammad Akbal; Imam Suyitno (Universitas Negeri Makassar, 2022)
This study aims to identify and examine the occurrence of a single candidate for Regent and Deputy Regent in the general election for the regional head of Gowa Regency in 2020. This study uses a qualitative research type with a descriptive approach. Based on the source, the types of data used are primary data and secondary data. Primary data were obtained through interviews with community leaders, religious leaders, youth leaders in Gowa Regency, the chairman of the Gowa Regency KPUD, and members of the Gowa Regency DPRD as well as documentation. While secondary data is data obtained from various literatures such as books, journals, laws and other related sources. Processing and presentation of data is done descriptively. The results of the study show that the occurrence of a single candidate for Regent and Deputy Regent in the general election for the regional head of Gowa Regency in 2020 is caused by several factors, including: a). the couple Adnan Purrichta Ichsan and Abdul Rauf Mallagani were already known to most of the people of Gowa Regency before, b). There was a role or involvement of a number of figures, c). inseparable from the performance and achievements of Adnan Purrichta Ichsan and Abdul Rauf Mallagani in the previous period, d). and the absence of other candidates who appeared against the pair Adnan Purrichta Ichsan and Abdul Rauf Mallagani either from the political party line or from the individual line.